Uji Stabilitas dan Uji Aktivitas Antifungi Sediaan Krim Dari Fraksi Etil Asetat Daun Matoa (Pometia pinnata J.R Forst & G. Forst) Terhadap Pertumbuhan Jamur Trichophyton rubrum - Agus Rahman Rinaldi; Devahimer Harsep Rosi; Linda Hevira (Herbal Medicine Journal, 2026)
Matoa (Pometia pinnata) is one of the endemic plants of Papua that has pharmacological antifungal activity. This study aimed to determine whether the ethyl acetate fraction of Matoa leaves can be formulated into a cream preparation that meets the requirements for stability testing and antifungal activity testing. This study is an experimental study which includes stability testing and antifungal activity testing of the cream preparation made from the Matoa leaf fraction against the growth of the fungus Trichophyton rubrum. The yield of ethanol extract from Matoa leaves was 21.272%, which had organoleptic properties that did not differ among each cream formula. The cream formulas were homogeneous, with no coarse granules observed during homogeneity testing. The pH of the cream preparations was between 4 and 5. The adhesive and spreading power of the cream preparations met the requirements, except for formula F3. The antifungal activity of the ethyl acetate fraction cream preparations against Trichophyton rubrum showed inhibition zones as follows: F1: 18.28 mm, F2: 11.19 mm, and F3: 18.81 mm. All formulas (F1, F2, and F3) met the physical and stability requirements for a good cream preparation, except that the spreading power test for F3 did not meet the criteria for good cream physical properties. The best antifungal activity against Trichophyton rubrum was observed in formula F3, with an inhibition zone of 18.81 mm, categorized as strong antifungal activity.